1989
DOI: 10.1111/j.1600-0765.1989.tb02000.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressed helper‐to‐suppressor T‐cell ratios in early‐onset forms of periodontal disease

Abstract: Helper (CD4+)-to-suppressor (CD8+) T-cell ratios were determined by flow cytometry for 12 patients with early-onset forms of periodontal disease and their appropriate controls. When considered as a group, patients with early-onset periodontal disease showed a markedly depressed CD4+/CD8+ ratio relative to controls (means 0.92 and 1.50 respectively). This difference was significant at the 0.0015% level as determined by the Mann-Whitney test. Separate analysis of patients with either the juvenile or rapidly prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
2
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 15 publications
3
33
2
1
Order By: Relevance
“…If juvenile periodontitis (IP) and rapidly progressive periopresent, an elevated CD4:CD8 ratio may be attributable dontitis (RPP) (Kinane et al, 1989), others have found this to a decrease in the number of CD8+ cells (Nagasawa et ratio to be elevated relative to healthy controls (Katz et al, 1995;Takahashi etal., 1995), although again this is not a consistent finding (Celenligil et al, 1990a;Afar et al, 1992). The conflicting results from these studies may be due to the large variability of the values within patient groups (Katz et al, 1988;Takahashi et al, 1995 (Mahanonda et al, 1989(Mahanonda et al, , 1991.…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphomentioning
confidence: 99%
“…If juvenile periodontitis (IP) and rapidly progressive periopresent, an elevated CD4:CD8 ratio may be attributable dontitis (RPP) (Kinane et al, 1989), others have found this to a decrease in the number of CD8+ cells (Nagasawa et ratio to be elevated relative to healthy controls (Katz et al, 1995;Takahashi etal., 1995), although again this is not a consistent finding (Celenligil et al, 1990a;Afar et al, 1992). The conflicting results from these studies may be due to the large variability of the values within patient groups (Katz et al, 1988;Takahashi et al, 1995 (Mahanonda et al, 1989(Mahanonda et al, , 1991.…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphomentioning
confidence: 99%
“…(Fenesy, 1998). Epidemiological evidence indicates the existence of high risk groups and suggests that a variety of disease markets (risk factors) may predispose individuals to periodontitis Johnson et al (1988) Some forms of increased disease susceptibility or intrinsic defects may be involved in patients with EOP; for example, neutrophil dysfunction Van Dyke et al (1985), abnormal lymphocyte subsets Kinane et al 1989), and aberrant cytokine production Page et al (1985). Furthermore, a high prevalence of EOP patients in certain families and linkage with specific human leukocyte antigen (HLA) phenotypes have suggested that genetic factors may be involved in some cases and "Common risk factors" have been pointed out in these families.…”
Section: General Blood Examinationmentioning
confidence: 99%
“…A. actinomycetemcomitans releases several virulence factors, such as endotoxin and leukotoxin (6), and the infection is accompanied by local and systemic humoral immune responses (5). Earlier studies demonstrated an altered CD4/CD8 T-cell ratio and autologous mixed-lymphocyte reaction in LJP (14), suggesting a potential regulatory role of T cells in periodontitis. Some A. actinomycetemcomitans-specific CD4 ϩ T cells could migrate to rat periodontal tissues and mediate immune protection (4,33), suggesting that CD4 ϩ T cells play a role in host periodontal defense.…”
mentioning
confidence: 99%